Toward Valid Measures of Public Sector Productivity: Performance Measures in Urban Transit - Gleason, John M.; Barnum, Darold T. (Management Science, 1982)
In recent years, performance measurement has become the focus of attention in a variety of public sector fields. Unfortunately, too little has been done to develop valid operational definitions of performance, or to identify the weaknesses and biases inherent m certain types of performance measures. Thus, the potential exists for the inappropriate use of certain indicators in performance evaluations and decisions. One field in which there has been increasing effort to deal with performance problems is that of transit. Regardless, the nebulous nature of “performance” has been all too apparent in this industry. The terms “productivity,” “efficiency,” and “effectiveness” have been used synonymously in some instances, while in other cases “efficiency” and “effectiveness” have been considered to be different aspects of overall “productivity.” This confusion is of major significance, because the use of performance measures in operations assessment, decision making, and resource allocation is increasing. Furthermore, since it increasingly is being urged that subsidy payments be linked to the performance of a transit system, and since subsidies now constitute over half of transit revenues, the performance measurement problem is particularly important. This paper examines weaknesses and biases inherent in commonly used measures of urban mass transit performance. It is shown that measures of efficiency, such as cost per passenger, are being incorrectly used as measures of effectiveness and that various traditional measures of efficiency, such as those which incorporate mileage, can be misleading when applied in decision making. Suggestions are made for developing valid performance indicators and for developing safeguards that will avoid present shortcomings.